1988
DOI: 10.1073/pnas.85.5.1327
|View full text |Cite
|
Sign up to set email alerts
|

Role of algal eukaryotes in subtidal columnar stromatolite formation

Abstract: Columnar stromatolites were abundant and widespread in the Proterozoic but are exceedingly rare in modern seas. Consequently, the stromatolites at Hamelin Pool in Shark Bay, Western Australia, have been widely interpreted as unique modern analogs of ancient stromatolites constructed by complex communities of cyanobacteria. However, the Shark Bay columnar stromatolites contain sediment that is unusually coarse for stromatolites both ancient and modern, and the subtidal columnar stromatolites have a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
3
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 9 publications
2
90
3
2
Order By: Relevance
“…This difference in grain-size has been noted in present-day marine coarse-grained carbonate stromato lites formed by stabilisation (trapping and binding) of previously mo bile grains by microbial mats (Logan, 1961;Monty, 1976;Dravis, 1983;Reid and Browne, 1991;Riding et al, 1991a;Reid et al, 1999). In these examples, grain-trapping is produced by erect filaments, mat ir regularities, and extracellular polymeric substances (EPS) secreted by cyanobacteria and other mat microbes (Logan, 1961;Playford and Cockbain, 1976;Dravis, 1983;Dill et al, 1986;Awramik and Riding, 1988;Riding et al, 1991a;Visscher et al, 1998;Reid et al, 2000;Decho et al, 2005;Dupraz et al, 2009;Browne, 2011;Bowlin et al, 2012;jahnert and Collins, 2012). Rare filaments in some mixed laminae of the Leza coarse-grained stromatolites (Fig.…”
Section: Grain-rich Laminaementioning
confidence: 99%
See 1 more Smart Citation
“…This difference in grain-size has been noted in present-day marine coarse-grained carbonate stromato lites formed by stabilisation (trapping and binding) of previously mo bile grains by microbial mats (Logan, 1961;Monty, 1976;Dravis, 1983;Reid and Browne, 1991;Riding et al, 1991a;Reid et al, 1999). In these examples, grain-trapping is produced by erect filaments, mat ir regularities, and extracellular polymeric substances (EPS) secreted by cyanobacteria and other mat microbes (Logan, 1961;Playford and Cockbain, 1976;Dravis, 1983;Dill et al, 1986;Awramik and Riding, 1988;Riding et al, 1991a;Visscher et al, 1998;Reid et al, 2000;Decho et al, 2005;Dupraz et al, 2009;Browne, 2011;Bowlin et al, 2012;jahnert and Collins, 2012). Rare filaments in some mixed laminae of the Leza coarse-grained stromatolites (Fig.…”
Section: Grain-rich Laminaementioning
confidence: 99%
“…Although present-day coarse-grained carbonate examples are well known in the Bahamas and Shark Bay, grainy carbonate laminae are rarely the main components of ancient stromatolites (see Monty, 1977;Awramik and Riding, 1988;FairchHd, 1991;Altennann, 2008;Browne, 2011). Riding et al (1991b, Arenas and Pomar (2010) and Bourillot et aL (2010) studied examples of coarse-grained carbon ate stromatolites of Messinian (late Miocene) age in Spain, and Immenhauser et al (2005) described Aptian (Early Cretaceous) microbial build ups with crudely-layered coarse-grained carbonate microfabrics in Oman.…”
Section: Other Ancient Examples Of Coarse-grained Carbonate Stromatolmentioning
confidence: 99%
“…The interior of HPS1 (Figure 1c) also showed that this sample consisted of similar fine grains. These both resembled the intertidal finegrained stromatolites built by cyanobacteria as described in earlier studies by Awramik and Riding (1988). All samples were stored at 4 1C and DNA extraction and microorganism isolation were conducted immediately upon sample return.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have characterized growth rates of Hamelin Pool stromatolites by radiocarbon dating (12). Other studies have focused on the sedimentology (see, for example, reference 37), culture, and phylogeny of specific microorganisms (9,36), biomolecular pigments (41), ecological relationships (3), and microscopy (5). Such studies have generally presumed or concluded that cyanobacteria, and in some cases photosynthetic eucaryotes, are the main constituents of Hamelin Pool stromatolite communities.…”
mentioning
confidence: 99%